AI-Assisted Computational Thinking-Based Digital Worksheet in the Context of Deforestation to Improve Students’ Mathematical Problem-Solving Skills - Tampubolon, Farah Nabilah; Hapizah, Hapizah; Meryansumayeka, Meryansumayeka (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
This development research aimed to design an Artificial Intelligence (AI)-assisted, Computational Thinking (CT)-based digital worksheet on the Two-Variable Linear Equation System (SPLDV) topic within a deforestation context, and to examine its validity, practicality, and effectiveness in supporting students’ mathematical problem-solving skills. Although CT-based worksheets, AI-assisted learning, and environmental contexts have been studied separately, few studies have integrated these three components simultaneously in SPLDV learning; this study addresses that gap. Using the Design Research–Development Studies approach (preliminary research, prototyping, and assessment phases), the study involved grade VIII students of SMP IT Indo Global Mandiri Palembang, selected through purposive sampling (3 students in the one-to-one trial, 6 in the small-group trial, and 20 in the field test). Data were collected through observation, interviews, questionnaires, and tests, then analyzed descriptively and using the Normalized Gain (N-Gain) test and a paired-sample t-test. The digital worksheet was categorized as very valid (95.55%) and very practical (89.7%). Students’ average problem-solving score increased from 42.44 to 76.06 (N-Gain = 0.60, medium category; t = 11.13, p < 0.001). Within the scope of this single-school trial, the AI-assisted CT-based digital worksheet shows promise as a contextual mathematics teaching material.